Hierarchical risk parity portfolio design of traditional risky assets and cryptocurrencies in the Philippines - Edra, Jan Marie Claire J. (Animo Repository, 2023)
The Philippines saw the heightened interest of the investing public in cryptocurrencies when digital assets began gaining popularity, especially during the COVID-19 pandemic. This study introduces a portfolio of bonds, stocks, and foreign currency in the Philippines, combined with cryptocurrencies, by applying a method based on graph theory and machine learning techniques – the hierarchical risk parity approach. An out-of-sample comparison with traditional portfolio strategies shows that the hierarchical risk parity portfolio outperforms in terms of risk-adjusted return. The identified optimal portfolio reveals that only a small portion of the investment shall be allocated to cryptocurrencies, and much of the capital should still be with conventional assets.